Analisis Sebaran Spasial Kerentanan Longsor Sebagai Upaya Mitigasi Bencana di Kecamatan Berastagi Kabupaten Karo Provinsi Sumatera Utara - Dinda Ayu Pertiwi Sitorus; Slamet Bejo; Said Muzambiq (Jurnal Serambi Engineering, 2021)
Kabupaten Karo has several areas that have the potential to occurrence of a landslide.Therefore, the mitigation  of landslide disaster is very important,  it has long-term negative impacts on  humanity and the environment. This study attempts to analyze the distribution of vulnerability landslides in Berastagi mitigation and management and provide the right environment. The causes of a movement occur  landslides in Berastagi is the state  of a steep slope around 35, 55 % - percent of lithological building materials / unstable material among other volcanic breccias and, riodasit tufa and the factor triggering  rainfall andinfiltration water . The research method was descriptive , whereas scoring with  Shapefile (SHP) data in 2019 was based on the 2004 Puslittanak. The results of the field are the weightings of the respective parameter with overlay uses arcgis 10.6 software. The result showed that the DouluVillage, SempaJaya Village, Raya Village, as well as Tambak Lau Mulgap II in the Berastagi District have a high vulnerability to landslides. Thus, recommendations  for mitigation of calamity , by revegetation  erosion including  planting  crops.